Clinical Applications of Neuropsychoanalysis: Hypotheses Toward an Integrative Model - Flores Mosri, Daniela (Frontiers in Psychology, 2021)
Neuropsychoanalysis has been established as a field based on the dialog between psychoanalysis and the neurosciences. Freud was a neurologist for 20 years and used the neuroscientific knowledge of his time as the foundation of his metapsychology. Psychoanalysis has predominantly relied on its own method to develop techniques for the different psychoanalytic treatments. It rarely uses contribution from fields outside psychoanalysis that could enrich its understanding of the mind. Neuropsychoanalysis has informed and revised several topics in psychoanalysis, for example consciousness and the unconscious, dreams, and affect amongst many others. Clear clinical applications of neuropsychoanalysis can be appreciated in the work with neurological patients. However, a constant question from clinicians is whether neuropsychoanalytic findings can contribute to psychoanalytic treatments with non-neurological patients. This paper explores clinical applications of neuropsychoanalysis mainly based on affective neuroscience to propose an analysis of emotions that may contribute to the gradual development of a neuropsychoanalytically informed psychotherapy. The task of integrating neuroscientific knowledge into psychoanalytic technique is still considered a challenge of accentuated complexity, but it is at the same time a necessary and promising endeavor that aims at improving the quality of the treatments available for human suffering and psychopathology.